Presenilin/γ-secretase and inflammation - Saura, Carlos A. (Frontiers in Aging Neuroscience, 2010)
Presenilins (PS) are the catalytic components of γ-secretase, an aspartyl protease that regulates through proteolytic processing the function of multiple signaling proteins. Specially relevant is the γ-secretase-dependent cleavage of the β-amyloid precursor protein (APP) since generates the β-amyloid (Aβ) peptides that aggregate and accumulate in the brain of Alzheimer´s disease (AD) patients. Abnormal processing and/or accumulation of Aβ disrupt synaptic and metabolic processes leading to neuron dysfunction and neurodegeneration. Studies in presenilin conditional knockout mice have revealed that presenilin-1 is essential for age-dependent Aβ accumulation and inflammation. By contrast, mutations in the presenilin genes reponsible for early onset familial AD cause rapid disease progression and accentuate clinical and pathological features including inflammation. In addition, a number of loss of function mutations in presenilin-1 have been recently associated to non-Alzheimer's dementias including frontotemporal dementia and dementia with Lewy bodies. In agreement, total loss of presenilin function in the brain results in striking neurodegeneration and inflammation, which includes activation of glial cells and induction of proinflammatory genes, besides altered inflammatory responses in the periphery. Interestingly, some non-steroidal anti-inflammatory drugs (NSAIDs) that slow cognitive decline and reduce the risk of AD, decrease amyloidogenic Aβ42 levels by modulating allosterically PS/γ-secretase. In this review, I present current evidence supporting a role of presenilin/γ-secretase signaling on gliogenesis and gliosis in normal and pathological conditions. Understanding the cellular mechanisms regulated by presenilin/γ-secretase during chronic inflammatory processes may provide new approaches for the development of effective therapeutic strategies for AD.